The Hardy-Littlewood Theorem and the Operator of Harmonic Conjugate in Some Classes of Simply Connected Domains with Rectifiable Boundary - Tkachenko, N. M.; Shamoyan, F. A. (Журнал математичної фізики, аналізу, геометрії, 2009)
The analogue of known theorem Hardy-Littlewood about $L^p$-estimations of derivative analytical function through norm to the function, also are proved $L^p$-weight estimations the operator of harmonic conjugate in some classes of simply connected domains with rectifiable boundary for all $0<p<+∞$. Mathematics Subject Classification: 32A10, 45F05, 47B35, 47B30.